Buffalo farming in Greece: Present and future - Roustemis D.; Ragkos A.; Patousis D.; Theodoridis A.; Savvidou S. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Buffalo livestock farming (Bubalus bubalis) in Greece has been demonstrating a stable increase during the past 30 years, from only 312 animals in 1984 to 3,563 animals in 2014. This development occurred simultaneously with considerable developments in Greek markets with the emergence of modern enterprises with export orientation, increased demand for buffalo meat by Greeks – nonetheless not for dairy products – and public awareness concerning the two-fold environmental role played by buffalo farming: protection of indigenous genetic resources and development of wetland rangelands. This study presents the current situation in the sector, through the processing of reproduction and technical/economic data describing the operation of the system, provided by the Greek Buffalo Farmers’ Cooperative. These farms operate under an extensive or semi-intensive pattern, with low investments in infrastructure and high use of rangelands, as concentrates and forage are provided only during harsh winter periods. It is estimated that a farm of an average size of 40-70 females is viable under the extensive and semi-intensive system respectively. Based on the data, a set of structural measures is proposed to favor the sector.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)